2014
DOI: 10.1309/ajcp53kmhnrdicbl
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Performance of the BD Onclarity HPV Assay Using an Adjudicated Cohort of BD SurePath Liquid-Based Cytology Specimens

Abstract: The clinical performance of The BD Onclarity HPV Assay with respect to histology end points was similar to HC2. Moreover, discordant analysis revealed improved performance of the BD assay with respect to ability to provide extended genotyping information and lack of cross-reactivity with low-risk HPV types associated with cellular abnormalities. The relative risks for CIN 3 disease for HPV 31 and HPV 33/58 (combined) were comparable to that of HPV 18 in this population, suggesting that these genotypes may warr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
41
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 22 publications
5
41
0
1
Order By: Relevance
“…The agreement was found to be very high, even though the Onclarity test, with its extended genotype readout, represents a more complex diagnostic system than does the HC2. These findings are in line with the conclusions previously reported by Wright et al and Ejegod et al (17,18). Onclarity offers substantial advantages over "yes/no" assays like HC2 in terms of automation, reduced hands-on time, and the presence of an internal control based on a human housekeeping gene, the positivity of which confirms the adequacy of the specimen.…”
Section: Discussionsupporting
confidence: 92%
“…The agreement was found to be very high, even though the Onclarity test, with its extended genotype readout, represents a more complex diagnostic system than does the HC2. These findings are in line with the conclusions previously reported by Wright et al and Ejegod et al (17,18). Onclarity offers substantial advantages over "yes/no" assays like HC2 in terms of automation, reduced hands-on time, and the presence of an internal control based on a human housekeeping gene, the positivity of which confirms the adequacy of the specimen.…”
Section: Discussionsupporting
confidence: 92%
“…The pooled relative sensitivity and specificity estimates were 0.995 (95% CI, 0.958 to 1.033; I 2 ϭ 0.0%; P ϭ 0.554 for heterogeneity) and 0.988 (95% CI, 0.975 to 1.001; I 2 ϭ 0.0%; P ϭ 0.997 for heterogeneity), respectively. No heterogeneity was induced by the use of two different comparator tests, i.e., the HC2 assay in the studies by Wright et al (24) and Ejegod et al (5) and the GP5ϩ/6ϩ EIA in the present study.…”
Section: Discussionmentioning
confidence: 46%
“…In a multicenter U.S. study of the Onclarity assay using 541 archived samples, Wright and colleagues (24) reported the sensitivity and specificity of the assay for CIN2ϩ as 90.4% (95% CI, 83 to 95%) and 76.9% (95% CI, 73 to 81%), respectively, which are lower than the values reported in the present study, i.e., 96.1% (95% CI, 94.8 to 97.4%) and 89.1% (95% CI, 87.0 to 91.2%), respectively, and also lower than those reported by Ejegod et al (5). Again, the different populations must be considered; the U.S. study involved a younger population and histological "adjudication" by a review panel of pathologists, whereas, in the study by Ejegod et al (5) and the present study, the histological results were those derived from routine practice and were not reviewed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The BD Onclarity HPV Assay is a multi-plex Real-Time PCR assay that targets HPV type-specific E6 or E7 sequences [13]. The assay detects 14 HPV types, providing extended genotyping information.…”
Section: Methodsmentioning
confidence: 99%